THE POSSIBILITY OF PRODUCTION OF NON TRADITIONAL ENERGY BASED ON THE NATURAL RESOURCES - T., NazaravKh; L.Z., Ibragimov; Z.A, Ganiyev (International Journal of Psychosocial Rehabilitation, 2020)
Possibilities of taking electricity from Mirzachul oasis natural resources (water, wind, oxygen) (A case study of Mirzachul oasis) will be analyzed. Moreover, suggestions and recommendations will be given based on rational use of energy resources.